Structural, Optical and Electrical Characterization of Porous Silicon Prepared by DC and AC Electrochemical / \c Husnen R. Abd - Husnen R. Abd (Institute of Nano Electronic Engineering , University Malaysia Perlis, 2014)
This thesis undertakes the fabrication, optimization, characterization and analysisof metal - semiconductor-metal photodetector device (MSM -PD) based on PS. This study has examined n-type (100) orientation using direct current photoelectrochemical etching (DC-PECE) at different etching times, and also alternating current photoelectrochemcal etching (AC-PECE) using different etching current density.